Mother Jones and her army of Mill Children - Winter, Jonah, 1962- (Schwartz & Wade, 2020)
The story of Mother Jones, an Irish immigrant who was essential in the fight to create child labor laws. Well into her sixties, Mother Jones had finally had enough of children working long hours in dangerous factory jobs, and decided she was going to do something about it. The powerful protests she organized earned her the name "the most dangerous woman in America." And in the Children's Crusade of 1903, she lead one hundred boys and girls on a glorious march from Philadelphia right to the front door of President Theodore Roosevelt's Long Island home. -- adapted from amazon.com